Educators' and Learners' Responses to Optimising the Development of Arabic Teaching Module Based on the Merdeka Curriculum - Al Muhibbin, Fateh; Amrulloh, Muhammad Afif; Wahidah, Yeni Lailatul; Fauziah, Asti; Daoed, Dessy Sintari (Institut Agama Islam Negeri Curup, 2024)
This study aimed to develop an Arabic teaching module based on the Merdeka curriculum for grade IV of Asasalam Islamic Elementary School Bandar Lampung and to analyze educators’ and students’ responses to the teaching module. A teaching module is an important part of learning implementation. Moreover, the implementation of the Merdeka curriculum must also be harmonized with the existence of teaching module. However, Assalam Islamic Elementary School in Bandar Lampung, which has implemented the Merdeka curriculum, does not yet have a teaching module / teaching materials based on the Merdeka curriculum. The type of research employed in this study was Research and Development (R&D) with the ADDIE model. Data collection involved conducting interviews with Arabic language subject teachers at Assalam Islamic Elementary School. The instruments utilized in this development included student questionnaires and product validation instruments. Data analysis techniques encompassed qualitative descriptive and quantitative descriptive methods. Qualitative descriptive analysis was utilized to process data from the review of material experts, media experts, and field practitioners' responses, including teachers and students. Quantitative descriptive analysis was derived from the results of product feasibility, represented in the form of product practicality. The validation results from media experts yielded an average value of 86%, while those from material experts showed an average value of 93%, categorized as very feasible. Furthermore, the average response from educators was 93%, falling into the attractive category. The responses from students in small group trials averaged 91%, whereas in field trials, the average was 83%. Based on the findings of this study, it is evident that the teaching module is highly engaging for use in the learning process. This research contributes to the development of Arabic teaching module based on the Merdeka curriculum.